Evaluating an Applied Behavior Analysis Telehealth Training Package for Caregivers of Children With Autism in the Czech and Slovak Regions - Sheri Kingsdorf; Karel Pančocha
In places where in-person applied behavior analysis (ABA) services are not available to those in need, distance approaches may be needed. However, in the Czech Republic and surrounding countries, ABA and telehealth practices are just emerging. Therefore, minimal systems are guiding ABA-based telehealth for children with autism and their caregivers. To develop a model of low-cost, high-efficacy, family-centered, and fidelity-driven ABA telehealth services in Central Europe, this study piloted a systematic remote training package to teach caregivers to build foundational skills with their children with autism. Using a multiple baseline across behaviors design, practitioners followed scripts to collaboratively select targets and use behavioral skills training procedures with caregivers. Based on caregiver needs, their skill acquisition was evaluated in the skill sets of pairing, responding to challenging behaviors, and/or language building. Results demonstrated that the program was socially valid, contributed to skill gains, and increased quality of life.